Porno? Chic!: how pornography changed the world and made it a better place - McNair, Brian (Routledge, 2013)
Porno? Chic! examines the relationship between the proliferation of pornography and sexualised culture in the West and social and cultural trends which have advanced the rights of women and homosexuals. Brian McNair addresses this relationship with an analysis of trends in sexualised culture since 2002 linked to a transnational analysis of change in sexual politics and sex/gender relations in a range of societies, from the sexually liberalised societies of advanced capitalism to those in which women and homosexuals remain tightly controlled by authoritarian, patriarchal regimes. In this accessible, jargon-free book, Brian McNair examines why those societies in which sexualised culture is the most liberalised and pervasive are also those in which the socio-economic and political rights of women and homosexuals have advanced the most.
Section: xii, 188 p. : ill. ; 24 cm
Keywords: LGBTQIA2+; approches et analyses; communication; cours; discipline; droits des femmes*; féminisme pop; identités LGBTQIA2+; justice sociale; premier cycle; queer; sciences humaines; sciences sociales; sex1911; sexualité; thématiques; études culturelles

The feminist porn book: the politics of producing pleasure - Taormino, Tristan; Shimizu, Celine Parreñas; Penley, Constance; Miller-Young, Mireille (The Feminist Press at the City University of New York, 2013)
''This book brings together writings by feminists in the adult industry and research by feminist porn scholars. It investigates not only how feminists understand pornography, but also how feminists do porn - that is, direct, act in, produce, and consume this kind of 'industry'. With contributions by Susie Bright, Candida Royalle, Betty Dodson, Nina Hartley, Buck Angel, Lynn Comella, Jane Ward, Ariane Cruz, Kevin Heffernan, and more.''– Fourni par l'éditeur.
Le texte Lavigne, J. (2017). Autopornography and the struggle for the recognition of a sexual subjectivity: a theoretical analysis from Loree Erickson's testimony a été donné en lecture au cours SEX1920
Keywords: approches et analyses; arts; arts visuels et médiatiques; cinéma; communication; corps; cours; discipline; féminisme pop; féminisme pro-sexe; histoire et politique; premier cycle; ressource en ligne; sciences humaines; sex1911; sex1920; sexologie; sexualité; thématiques